The Effectiveness of Using Laser Therapy on Outcome of Carpal Tunnel Syndrome Patients : A Literature Review - Tjahyanto, Teddy; Mayung, Claraiva; Yohanes, Guntur; Erwin, Ferdinand; Wiracakra, I Gusti Lanang Krisna (International Journal of Public Health Excellence (IJPHE), 2023)
Carpal Tunnel Syndrome (CTS) is a neuropathy caused by compression of the median nerve that passes through the carpal tunnel structure in the wrist. If the CTS condition is not treated, complications will occur such as irreversible damage to the median nerve resulting in permanent impairment and disability, chronic wrist pain, and muscle atrophy and weakness. Currently there are various CTS therapies such as splinting , local injection of corticosteroids, oral medications such as prednisone, physical therapy such as carpal bone mobilization, ultrasound therapy , and nerve glides exercises , as well as surgical therapy. However, these various therapies have not provided optimal results and there are complications such as neuromas, hypertrophic wounds, dysesthesia, wrist joint stiffness, and the inability of various to reduce CTS symptoms. Therefore, more effective therapy with minimal side effects is needed. Therefore, in this literature review, an analysis of the effect of laser therapy on various outcomes of CTS patients as an innovative therapy was carried out. Study searches were performed on various databases such as Pubmed, ScienceDirect , Directory of Open Access Journal , Epistemonikos, and Cochrane Library . From the search results obtained a total of 389 studies. The 7 studies that met the inclusion and exclusion criteria were the studies that were analyzed in this literature review. Various types of laser therapy showed better outcome results than the control group, with LLLT laser therapy showing the best results in various outcomes in CTS patients. LLLT laser therapy also shows better results when combined with other types of therapy. No adverse events were reported with any type of laser therapy in all inclusion studies. Therapy is the newest type of innovative therapy with better effects and minimal side effects compared to conventional therapy in CTS patients.